2018
DOI: 10.1007/s10661-018-7033-4
|View full text |Cite
|
Sign up to set email alerts
|

Household-stored drinking water quality among households of under-five children with and without acute diarrhea in towns of Wegera District, in North Gondar, Northwest Ethiopia

Abstract: Contamination of drinking water in household water storage containers and inadequate water supplies are common public burdens in low- and middle-income countries, including towns in Wegera District, Ethiopia. Our study aimed to assess the quality of drinking water and identify factors associated with diarrhea in households with under-five (U5) children with and without diarrhea in Ambagiorgis and Gedebge towns in Wegera District. Stored drinking water samples from households with U5 children with and without d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
(35 reference statements)
4
18
0
1
Order By: Relevance
“…While changing routines is a commonly identified coping strategy (Smiley, 2016;Thompson et al, 2000), it is difficult to find accounts that include the associated loss of livelihood. Similarly, household water storage, another important coping and adaptation strategy, is commonly found in both our findings and the broader literature (Smiley, 2016;Thompson et al, 2000) but is likely to also affect water quality, as untreated bacteria in buckets and tanks frequently lead to water-borne diseases (Feleke et al, 2018). Thus, although all our participants blamed health challenges such as stomach ache and diarrhoea on the poor quality of the water provided by the WUC, it is important to note that they could have other causes.…”
Section: Discussionsupporting
confidence: 54%
“…While changing routines is a commonly identified coping strategy (Smiley, 2016;Thompson et al, 2000), it is difficult to find accounts that include the associated loss of livelihood. Similarly, household water storage, another important coping and adaptation strategy, is commonly found in both our findings and the broader literature (Smiley, 2016;Thompson et al, 2000) but is likely to also affect water quality, as untreated bacteria in buckets and tanks frequently lead to water-borne diseases (Feleke et al, 2018). Thus, although all our participants blamed health challenges such as stomach ache and diarrhoea on the poor quality of the water provided by the WUC, it is important to note that they could have other causes.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, other studies in Ethiopia reported a high rate of total coliform prevalence of 77–100% [ 9 11 ] and 80 to 100% prevalence of faecal coliform [ 10 13 ] in the drinking water system. Drinking water pollution at the source, distribution line, or the household level has been a big public health concern in developing nations such as Ethiopia [ 12 – 16 ]. In this study, water samples from almost all the households' containers were found to be contaminated with coliforms, which strongly suggested poor handling practices at the household level.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted regarding the bacteriological quality of drinking water in the different localities of Ethiopia. For instance, a study in Jimma zone (south west Ethiopia) by Yasin et al [ 7 ] reported that all drinking water samples were tested positive for total and fecal coliforms; Tabor et al [ 8 ] reported that 77% of the drinking water samples in Bahir Dar city (Northwest Ethiopia) were tested positive for total coliform counts, and they had a high-risk score; a study by Berhanu and Hailu [ 9 ] in Bona District (southern Ethiopia) showed that 86% of the drinking water did not meet the WHO guidelines for drinking water qaulity; a study in Adama town (Eastern Ethiopia) by Temesgen and Hameed [ 10 ] showed that 44.2% and 28.9% of the water samples were tested positive for fecal coliforms and fecal streptococcus, respectively; Feleke et al [ 11 ] reported fecal coliform count of 82.1 to 86.8% in drinking water in Wogera town (Northern Ethiopia); Duressa et al [ 12 ] reported total coliform count of 100% and fecal coliform count of 37% in drinking water sample in Nekemte town (Western Ethiopia); a study by Alemayehu et al [ 13 ] in the southern region showed that 44.7% and 50.9% of the drinking water samples were contaminated with E. coli and Enterococcus , respectively, and had a high-risk score; and a study by Gizachew et al [ 14 ] in Boloso Sore district (southern Ethiopia) reported that 91% and 44% of drinking water samples collected from households and the sources were tested positive for fecal coliforms.…”
Section: Introductionmentioning
confidence: 99%